Montana - Florio, Gwen, 1955-; Shaffer, Caroline; Blackstone Audio, Inc.; Recorded Books, LLC. (Ashland, Or. : Blackstone Audio, 2013)
Lola wants out of Montana but must stay as a potential witness and try to solve the case herself. This sure-footed journalist feels off balance in this part of her own country where the isolation compels people to rely upon each other in unsettling ways. While unraveling her friend's death, Lola learns the hard lessons of a bad economy and that human bonds matter more than career success, yet misses the warning signals that her own life is in danger.
Compact disc.
Title from container.
In container (17 cm.).
Narrated by Caroline Shaffer.
Keywords: Women journalists -- Fiction; Murder -- Investigation -- Fiction; Drug traffic -- Fiction; White people -- Relations with Indians -- Fiction; Blackfeet Tribe of the Blackfeet Indian Reservation of Montana -- Fiction; Montana -- Fiction; Mystery fiction; Audiobooks